Epistolarity and Sociopoetics in Rural Education - Cássia Elen Nunes de Almeida; Sabrina Stein; Ana Tereza Reis da Silva (Revista Brasileira de Educação do Campo)
This article analyzes the potential of sociopoetics and epistolary as promising methodological tools for decolonizing scientific practices in/on/about Rural Education. The analysis is organized into three parts. First, we situate the principles and challenges of Rural Education. Second, we conceptualize sociopoetics and epistolary, indicating their intersections with Rural Education. Third, by analyzing data from a study conducted at a rural school in the Brazlândia region of the Federal District, we seek to demonstrate how sociopoetics, combined with epistolary, fosters active listening, the appreciation of local knowledge, and the collective creation of knowledge. The analysis indicates that these approaches allow us to break with traditional scientific paradigms, ensuring the participation of the groups involved as co-producers of knowledge.